Efektivitas Komunikasi Customer Service dalam Membangun Loyalitas Nasabah - Widia Widia; Melantin Khanatri; Chelsea Olivia; Erma Dely (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to analyze the effectiveness of customer service communication in building customer loyalty. Effective communication is a crucial factor in fostering positive relationships between companies and customers, particularly in financial institutions that prioritize service quality. Customer service plays a frontline role in delivering information, handling complaints, and creating a positive service experience, which in turn enhances customer trust and loyalty. This study employed a qualitative method with a descriptive approach. Data were collected through direct field observations, in-depth interviews, and documentation. The data analysis process involved data collection, data reduction, data presentation, and conclusion drawing in order to obtain a comprehensive understanding of the research findings. The results indicate that effective customer service communication has a significant influence on customer loyalty. Communication that is clear, friendly, responsive, and empathetic can improve customer satisfaction and strengthen long-term relationships between customers and the institution. Good service not only provides convenience but also fosters trust and emotional attachment, which encourages customers to remain loyal to the company's services. Therefore, customer service communication skills are a crucial factor in supporting business sustainability and development.